Pengaruh Entrepreneurial Orientation Terhadap Financial Performance Melalui Supply Chain Integration dan Customer Satisfaction sebagai Variabel Intervening Pada Perusahaan Publik Sektor Manufaktur Di Surabaya Dan Sidoarjo - Vivi - Effendy; Devie Devie Devie (Business Accounting Review, 2016)
This study aimed to examine the significantly direct and positive affect of entrepreneurial orientation to supply chain integration, entrepreneurial orientation to customer's satisfaction, supply chain integration to financial performance, customer's satisfaction to financial performance on go public manufacturing firms in Surabaya and Sidoarjo. This study used quantitative approach, and the data obtained through the distribution of questionnaires and used ratio financial statement analysis to go public manufacturing firms in Surabaya and Sidoarjo processed by using SmartPLS software. This study showed that there was a positive and significant relationship of entrepreneurial orientation to supply chain integration, entrepreneurial orientation to customer's satisfaction, entrepreneurial orientation to financial performance, supply chain integration to financial performance, customer's satisfaction to financial performance, and supply chain integration to customer's satisfaction on go public manufacturing firms in Surabaya and Sidoarjo. Supply chain integration and customer's satisfaction became the intervening variables to entrepreneurial orientation and financial performance.